Experimental Test Bench Showcasing an X in the Loop Strategy for Fuel Cell Testing - Oswald, Tancrède; Weiß, Lukas; Wensing, Michael (2024)
In the quest for reduced cost and shorter development times for fuel cell systems in industrial applications, two major issues arise. First, the electrochemical behavior of fuel cell systems is inherently difficult to predict. Second, testing fuel cell systems is resource intensive. These issues compound: Setting up an accurate model of a fuel cell system incurs long testing periods for model validation. Further, it does not guarantee acceptable results outside the tested range or for other membrane electrode assembly compositions. To mitigate these two major issues an X in the Loop concept is proposed. Essentially, this is the direct integration of the test sample, here a single fuel cell, into the modelling environment of the whole system. In practice, two strategies with different levels of integration are defined. The first strategy consists of initially deducing the operating parameters of the sample cell from the fuel cell system model. Then, setting them to the sample cell in the test bench. The response of the test sample is finally used to validate the designed system or update the parameters of the fuel cell model. The second strategy is a step further towards the integration of the test sample into the model. Here, the core model of the fuel cell inside the fuel cell system model is completely replaced with the test sample, reducing the need for an accurate electrochemical model while improving the prediction of the behavior of the fuel cell system. Compared to previously proposed testing concepts, here the balance of plants is directly integrated through a digital emulator, leading to a closer representation of the complete system. Furthermore, the test bench results are looped back to the model at run-time leading to a closer match between testing conditions and the real world as well a reduced impact of inaccuracies in the modelling of the fuel cell. On the way to realizing this goal, an experimental test bench capable of showcasing working prototypes of the proposed operating strategies has been built.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Fuel Cells; Test equipment and instrumentation

X-in-the-Loop Concept for the Integration of Simulation and Experiment for Fuel Cell Systems - Oswald, Tancrède; Weiß, Lukas; Wensing, Michael (Kraftstoffe Für Die Mobilität Von Morgen, 2024)
Keywords: X-iL; Brennstoffzelle; Versuch; Simulation